Flip the switch : how to activate your drive to achieve a freakish level of success - Burt, Micheal J. (McGraw Hill-Ascent Audio, 2023)
Learn now to unlock your "prey drive"--The instinctual ability that allows you to "flip the switch" to achieve massive success Getting to the next level of success requires more than hard work and perseverance. In Flip the Switch, championship basketball turned business coach Micheal Burt shows you how the world's greatest achievers have learned to access their inner switch-an instinctive "prey drive" that allows them to passionately pursue a target or goal. We all have this switch, but it's impossible to access without knowing what drives us. In Flip the Switch, Coach Burt guides you through the five primary drivers that fuel motivation-fear, competition, exposure, environment, and embarrassment-and leads you through soul-searching questions to discover your own prey drive: What am I deeply passionate about? Where is there a need in the world that I can fulfill? What am I naturally talented at? What am I curious about? Armed with self-knowledge and self-directed motivation, you'll reach a higher plane of success than what hard work and perseverance brings; you'll discover what you're wired to do, naturally